PERBANDINGAN KETAHANAN PENYAKIT BULAI JENIS (Peronosclerospora Philippinensis dan Peronosclerospora Maydis) CALON VARIETAS JAGUNG HIBRIDA - Suntoko suntoko; Chitra Dewi Yulia Christie; Febri Hendrayana; Nia Agus Lestari (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
This study aims to compare the resistance of hybrid maize varieties from